Development of alpha tracks measurement with thermal oven as an etching technique for SSNTDs. (2021) - Kadhim, Nada Farhan; Ridha, Ali A.; Salim, Manar Dheyaa; Hanfi, M.Y.; Mostafa, Mostafa Y.A.
Abstract: In the present work, Thermal oven as a heating technique in chemical etching process has been tested to investigate the track density and compares with a traditional technique water bath (WB). Thermal oven induced chemical etching has been employed in reducing the etching duration. Two solid-state nuclear track detectors (SSNTDs) CR-39 and LR-115 are utilized in this comparison. Detectors are exposed to 226 Ra alpha source (5 µ ci). Several pieces of CR-39 and LR-115 detectors were exposed to 226 Ra source at three different times of exposure (5, 10 and 15sec). Chemically Etching carry out with NaOH alkaline solution (6.25 N) at 70 °C for CR-39 and (2.5 N) at 60 °C for LR-115. For (5, 10 and 15sec) exposure time, the estimated maximum track densities of CR-39 detector at 90 min for thermal oven compared with 120 min for water bath. LR-115 detector maximum track densities were founded at 40 min compared with 50 min for the water bath technique. Finally, the etching parameters (the diameter of the tracks (D), etching efficiency (ɳ), bulk etching rate (VB ), track etching rate (VT ), and the sensitivity (V)) were calculated and compared.